Lexicalizing directional and nondirectional motion in Emai - Ronald P. Schaefer (LibraryPress@UF, 1986)
Motion expressions in Emai, an Edoid language of Nigeria, are examined within the lexical typology of Talmy [1985]. Both directional and nondirectional motion structures involving the MANNER verb la 'to run' are analyzed, though only the former, syntactically expressed by verbs in continuous series, poses a particular problem for interpretation. Three hypotheses concerning the semantic composition of these serial verbs are considered and evaluated in terms of their distributional constraints. It is concluded that nondirectional motion can be lexicalized by either of two patterns [MOTION+MANNER] PATH or MOTION PATH ... MANNER, while directional motion allows only the single lexicalization pattern MANNER [MOTION+PATH]. Typologically, these reflect two of the incorporation patterns Talmy has identified as characteristic in languages of the world.